Analisis Knowledge Management Berbasis Kompetensi Profesional Guru Di Madrasah Aliyah Negeri 2 Kota Bandung - Raden Luzna Huwaida; Irawan; Heri Khoiruddin (Yayasan Al-Afif, 2025)
This study explores the application of knowledge management to enhance teacher professionalism at Madrasah Aliyah Negeri (MAN) 2 Bandung. As an institution that prioritizes employee competence, MAN 2 Bandung implemented a qualitative method with literature study analysis. Data were collected from primary sources (observations and interviews) and secondary sources (journals and articles). Using descriptive-analytic techniques, the study found that teacher professionalism has improved through knowledge management practices. Key activities include: (1) codifying and storing knowledge in a database accessible to authorized staff; (2) sending selected personnel to training programs to gain new knowledge; (3) inviting internal and external experts to share insights through school programs; and (4) encouraging independent exploration of knowledge through book reviews, research, prototypes, and Focus Group Discussions such as MGMP. These efforts demonstrate how structured knowledge management effectively strengthens teacher professionalism at MAN 2 Bandung.